Large scale backfill technology and equipment - Zhang, P.; Li, H.Y.; Shi, S.H. (Mine Fill 2014: Proceedings of the Eleventh International Symposium on Mining with Backfill, 2014)
In recent years, a number of large scale and deep underground metal mines have been developed in China, with proposed annual capacity generally exceeding 10 million tonnes. Where protecting the environment from surface subsidence, optimising recovery of ore resources and reducing the tailings storage requirements, the recommended approach is to fill with tailings backfill. Therefore, the study of large scale backfill technology and corresponding equipment becomes essential. Filling systems with tailings face new technical problems and challenges in large scale backfilling situations.